Digital transformation and its impact on inclusive growth: a four-decade experience in Indonesia - Kristyanto, Visi Saujaningati; Jamil, Hidsal (Jurnal Ekonomi & Studi Pembangunan, 2023)
The debate over whether digital transformation benefits or harms inclusive growth continues. Existing evidence in the literature, on the other hand, is frequently based on short study periods, subjective measurement issues, and endogeneity issues, resulting in less credible findings in previous studies. To address this gap, this study draws on four decades of Indonesian experience spanning 1980 to 2021, with a focus on two primary objectives. First, this study utilises Principal Component Analysis (PCA) to assess the key factors forming the progress of digital transformation and inclusive growth. Second, the Two-Stage Least Square (2SLS) estimation method is applied in this study to investigate the endogenous impact of digital transformation on inclusive growth. The PCA results show that medium and high-tech manufacturing play a dominant role in representing digital transformation, while GDP per capita growth and poverty alleviation are the primary contributors to measuring inclusive growth. The 2SLS estimation shows that digital transformation significantly promotes inclusive growth in Indonesia, with its impact closely related to the previous year's digital transformation status. When these findings are considered jointly, it is clear that the beneficial effects of digital transformation are mainly explained by how medium and high-tech manufacturing sectors can stimulate inclusive growth in the context of increasing GDP per capita and reducing poverty in Indonesia.